Basic english grammar - Schrampfer Azar, Betty (Basic english grammar)
Blending communicative and interactive approaches with tried-and-true grammar teaching, "Basic English Grammar, " Third Edition, by Betty Schrampfer Azar and Stacy A. Hagen, offers concise, accurate, level-appropriate grammar information with an abundance of exercises, contexts, and classroom activities. New features of "Basic English Grammar," Third Edition: Increased speaking practice through interactive pair and group work. New structure-focused listening exercises.More activities that provide real communication opportunities. Added illustrations to help students learn vocabulary, understand contexts, and engage in communicative language tasks. New Workbook solely devoted to self-study exercises. New Audio CDs and listening script in the back of the Student Book. Student Book is available with or without Answer Key. Student Book and Workbook are available in split versions.